Total Plate Count Test for Bacteria in Home industry Baby Porridge in the Malang City Area - Anis Akhwan Dhafin; Elsa Mahardika Dhafin; Faisal Akhmal Muslikh; Fendy Prasetyawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The growth and development of toddlers greatly influences the quality of human resources in the future so that the toddler years are an important period in human development. In nutritional development, food has an important role in growth. During the toddler years, apart from breast milk, babies also need additional food, namely MP-ASI. MP-ASI can be contaminated by chemical and biological contaminants, one of the biological contaminants in food is bacteria. The TPC (Total Plate Count) test is a test used to count the number of bacterial colonies in the media being tested. The stages carried out before testing are sample dilution and media formulation. This research aims to determine whether or not there are bacteria in samples of Home industry Baby Porridge sold in the city of Malang. The samples studied were 8 samples. The sampling technique was carried out by purposive sampling. Based on the research that has been carried out, it can be concluded that of the 8 samples of home industry baby porridge sold in the city of Malang, 2 samples meet the requirements with the condition that the number of colonies is 2 x 10 2 colonies/g. The remaining 6 samples did not meet the requirements.